Benchmarking as a modern effective tool for developing the economic and financial potential of electric grid companies - A. E. Chicherov (Путеводитель предпринимателя)
The complexity of managing the power grid complex consists in the monopoly character of the electric power transmission operations. This is the reason for the lack of motivation to improve resource efficiency and quality of services provided by such organizations. The study examines the experience of the Russian power grid companies efficiency benchmarking, find out disadvantages of the researches made earlier and proposes a method of the power grid companies operational efficiency benchmarking.